Effect of fructo-oligosaccharides and lactic acid bacteria on caecal swine fermentation: in vitro trials - A.M. Pulimeno; M.L. Callegari; F. Rossi (Italian Journal of Animal Science, 2011)
The expected ban for 2006 of non therapeutic use of antibiotics in livestock, makes binding the development of reliable alternatives. The use of LAB and oligosaccharides (OS) has sometimes produced disappointing results probably due to the inability of LAB to colonize the gastro intestinal tract or to metabolize OS...